1978
DOI: 10.1055/s-0038-1648635
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane Generation and Platelet Aggregation in Survivals of Myocardial Infarction

Abstract: SummaryArachidonic acid (AA)-induced platelet aggregation was studied in platelet-rich plasma of 30 male patients who survived myocardial infarction and in 30 healthy men of similar age. Mean platelet aggregation thresholds to A A were 746 ± 62 μM, and 869 ± 57 μM, respectively. Only in 2 healthy subjects, but in 12 patients, irreversible platelet aggregation was induced consistently with low concentrations of AA, under 500 μM. The rate of conversion of AA to thromboxane A2 (TXA2) by platelets of these patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

1980
1980
1999
1999

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(27 citation statements)
references
References 14 publications
3
24
0
Order By: Relevance
“…It has recently been shown that platelets from patients who have survived a myocardial infarction have a decreased aggregation threshold for arachidonic acid and increased production of thromboxane A2 (16). The results of our study indicate that sulphinpyrazone treatment would have a correcting effect on this.…”
Section: Discussionsupporting
confidence: 52%
“…It has recently been shown that platelets from patients who have survived a myocardial infarction have a decreased aggregation threshold for arachidonic acid and increased production of thromboxane A2 (16). The results of our study indicate that sulphinpyrazone treatment would have a correcting effect on this.…”
Section: Discussionsupporting
confidence: 52%
“…Activated platelets produce the potent vaso-constrictor and platelet aggregating agent thromboxane A217'8 by oxidation of endogenous arachidonic acid. Sulphinpyrazone, a cyclo-oxygenase inhibitor, interferes with its synthesis.8 This drug, given to normal subjects, impairs arachidonic acidinduced platelet aggregation and reduces platelet malondialdehyde production.9 Szczeklik et al 2 found increased sensitivity to arachidonic acid-induced aggregation and more rapid platelet synthesis of thromboxane A2 in patients who had had a myocardial infarction at least 3 months previously. Agents like sulphinpyrazone which inhibit cyclo-oxygenase, reduce the sensitivity of platelets to arachidonic acidinduced aggregation.8 In our study, patients after myocardial infarction showed a significantly increased sensitivity to arachidonic acid throughout the seven months of observation, the changes being already apparent when the patients were first evaluated within 24 hours of infarction, but becoming more marked over the next 3 days.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets from patients with arterial thrombosis, deep venous thrombosis, or recurrent venous thrombosis produce more PG endoperoxides and TXA 2 than normal and have a shortened survival time. 50 Platelets from rabbits made atherosclerotic by dietary manipulation 51 and from patients who have survived myocardial infarction 52 are abnormally sensitive to aggregating agents and produce more TXA 2 than controls. Elevated TXB 2 levels have been demonstrated in the blood of patients with Prinzmetal's angina 53 and vasotonic angina.…”
Section: Prostacyclin and Txa 2 In Diseasementioning
confidence: 99%